The meniscal tear outcome (METRO) review: a systematic review summarising the clinical course and outcomes of patients with a meniscal tear - Ahmed, I; Dhaif, F; Khatri, C; Parsons, N; Hutchinson, C; Staniszewska, S; Price, A; Metcalfe, A (Elsevier, 2022)
Background: Meniscal tears affect 222 per 100,000 of the population and can be managed non-operatively or operatively with an arthroscopic partial meniscectomy (APM), meniscal repair or meniscal transplantation. The purpose of this review is to summarise the outcomes following treatment with a meniscal tear and explore correlations between outcomes. Method: A systematic review was performed of MEDLINE, EMBASE, AMED and the Cochrane Central Register of Controlled Trials to identify prospective studies describing the outcomes of patients with a meniscal tear. Comparisons were made of outcomes between APM and non-operative groups. Outcomes were graphically presented over time for all treatment interventions. Pearson’s correlations were calculated between outcome timepoints. Results: 35 studies were included, 28 reported outcomes following APM; four following meniscal repair and three following meniscal transplant. Graphical plots demonstrated a sustained improvement for all treatment interventions. A moderate to very strong correlation was reported between baseline and three-month outcomes. In the medium term, there was small significant difference in outcome between APM and non-operative measures (SMD 0.17; 95 % CI 0.04, 0.29), however, this was not clinically significant. Conclusions: Patients with a meniscal tear demonstrated a sustained initial improvement in function scores, which was true of all treatments examined. APM may have little benefit in older people, however, previous trials did not include patients who meet the current indications for surgery as a result the findings should not be generalised to all patients with a meniscal tear. Further trials are required in patients who meet current operative indications.